Odpowiedzi

Najlepsza Odpowiedź!
2010-04-14T16:42:21+02:00
3(-x-3) > -27
-3x-9 > -27 /+9
-3x > -18 /:(-3)
6 > x


x+1 ≥ 0.8x+1 /-0,8x -1
0,2x ≥ 0
x ≥ 0


-2.5x + 3> 2.5-2x /+2,5x -2,5
0,5 > 0,5x
1 > x



- x/3-1 < -1/3 /+1
-x/3 < 2/3 /*3
-x < 2 /*(-1)
-2 < x


-x+3 /2 ≥ 1 /-3/2
-x ≥ -0,5 /*(-1)
0,5 ≥ x
2010-04-14T16:44:48+02:00
3(-x-3) > -27
-3x-9>-27
-3x>-27+9
-3x>36/:-3
x>12

x+1 ≥ 0.8x+1
x-0,8x ≥-1+1
-1,8x ≥0

-2.5x + 3> 2.5-2x
-2,5x+2x>-3+2,5
-0,5x>-0,5/:-0,5
x>1

- x/3-1<-1/3/*3
-x<-1/:-1
x=1

-x+3 /2 ≥ 1 /*2
-2x+3 ≥2
-2x ≥-3+2
-2x ≥-1/:-2
x ≥0,5
2010-04-14T16:59:20+02:00
3(-x-3) > -27
-3x-9 > -27
-3x>-27+9
-3x>-18/:-3
x<6

x+1 ≥ 0.8x+1
x-0.8x ≥ 1-1
02x ≥ 0
równanie sprzeczne

-2.5x + 3> 2.5-2x
-2.5x+2x > 2.5 - 3
0.5x > -0.5 /: - 0.5
x<1

- x/3-1<-1/3 /*3
-x-3<-1
-x<-1+3
-x<2/:-1
x>-2

-x + 3/2 ≥ 1 /*2
-2x +3 ≥ 2
-2x ≥ 2-3
-2x≥ -1/:-2
x ≤ 1/2

Pozdrwiam :*